2021
DOI: 10.3390/ijms23010144
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage Polarity and Disease Control

Abstract: Macrophages are present in most human tissues and have very diverse functions. Activated macrophages are usually divided into two phenotypes, M1 macrophages and M2 macrophages, which are altered by various factors such as microorganisms, tissue microenvironment, and cytokine signals. Macrophage polarity is very important for infections, inflammatory diseases, and malignancies; its management can be key in the prevention and treatment of diseases. In this review, we assess the current state of knowledge on macr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
97
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(100 citation statements)
references
References 111 publications
(142 reference statements)
1
97
0
2
Order By: Relevance
“…The inflammation reaction is the first nonspecific response of the immune system associated with macrophages polarization into a pro-inflammatory status. They release inflammation mediators such as NO (vasodilation) and PGE-2 (immune reaction) among others [ 37 , 38 ]. These disturbances are involved in low-grade inflammation known to promote various metabolic diseases [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…The inflammation reaction is the first nonspecific response of the immune system associated with macrophages polarization into a pro-inflammatory status. They release inflammation mediators such as NO (vasodilation) and PGE-2 (immune reaction) among others [ 37 , 38 ]. These disturbances are involved in low-grade inflammation known to promote various metabolic diseases [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported the macrophage subsets contribute to inflammation (M1), anti-inflammation (M2a), and tissue remodeling phenotype (M2c). 30 – 33 Our previous study showed that stimulation of M1 polarization by IFN-Îł and LPS increased CD86 expression in mouse bone marrow– and disc-derived CD11b-positive cells in vitro. 7 In contrast, stimulation of M2a polarization by IL-4 promoted Fizz1 and CD206 and M2c polarization by increased CD206 expression in disc-derived CD11b cells.…”
Section: Discussionmentioning
confidence: 99%
“… Macrophage polarization. Different stimuli, surface and intracellular markers, secreted factors and biological responses [ 22 , 23 , 24 ] between M1 and M2 macrophages were summarized. Abbreviation: IFNÎł (interferon gamma); LPS (lipopolysaccharide); GM-CSF (granulocyte-macrophage colony stimulating factor); TNF (tumor necrosis factor); CD (cluster of differentiation); MHC-II (major histocompatibility complex class II); iNOS (inducible nitric oxide synthase); STAT (signal transducer and activator of transcription); TLR (toll-like receptor); Arg1 (arginase 1); FIZZ1 (resistin-like molecule alpha1); IL (interleukin); TGF-β (tumor growth factor-beta); MCSF (macrophage colony-stimulating factor); AMP (cyclic adenosine monophosphate); CCL (chemokine C-C motif ligand); CXCL (C-X-C motif ligand); ROS (reactive oxygen species); RNS (reactive nitrogen species); VEGF (vascular endothelial growth factor).…”
Section: Figurementioning
confidence: 99%